The intertidal polychaete (Annelida) fauna of the Sitakunda coast (Chittagong, Bangladesh), with notes on the Capitellidae, Glyceridae, Lumbrineridae, Nephtyidae, Nereididae and Phyllodocidae of the “Northern Bay of Bengal Ecoregion” - Muir, Alexander I.; Hossain, Md. M. Maruf. (ZOOKEYS, 2014)
Of seven species of polychaetous annelids collected from the intertidal zone of Sitakunda coast, Chittagong, Bangladesh, five were new records for the country. The seven are listed, with brief notes on these, some previously recorded species and others housed in the collections of the Natural History Museum, London. Keys are given to the recorded species of Phyllodocidae, Nereididae, Lumbrineridae, Nephtyidae and Capitellidae of the "Northern Bay of Bengal Ecoregion", and to the recognised species of Glyceridae from the Bay of Bengal. The worms in this Ecoregion are subject to the outflows of the Irrawaddy, Ganges, Hooghly and Mahanadi Rivers, and many of them are known to be freshwater tolerant.
World Polychaeta Database (WPolyDb)